Urban Strategic Planning from the Perspective of Well-Being: Evaluation of the Hungarian Practice - Bajmócy, Zoltán; Gébert, Judit; Málovics, György; Berki, Boglárka Méreiné; Juhász, Judit (European Spatial Research and Policy, 2020)
The present paper evaluates Hungarian strategic urban planning from the perspective of well-being. It conceptualises well-being in line with Amartya Sen’s capability approach (CA). We argue that the CA provides a meaningful concept of common good or public interest for evaluation. The open-ended nature of CA allows one to embrace the complexity of strategic planning, but it is definite enough to provide a clear normative framework for evaluation. We base our conclusions on 49 interviews with various local actors in three second-tier cities. We conclude that the CA-based evaluation can supplement the dominantly used conformance or performance-based evaluation approaches. We also found that instead of depicting an unachievable ideal state, the CA is able to provide guidance for feasible steps to further well-being.